The Spectrum of Endoscopic Ultrasound Intervention in Biliary Diseases: A Single Center’s Experience in 31 Cases - Siriboon Attasaranya; Nisa Netinasunton; Theeratus Jongboonyanuparp; Jaksin Sottisuporn; Teepawit Witeerungrot; Teerha Pirathvisuth; Bancha Ovartlarnporn (Gastroenterology Research and Practice, 2012)
Background and Aim. EUS-guided intervention (EGI) for biliary therapy has been increasingly used in recent years. This report aims to describe the spectrum and experience of EUS-guided interventions in biliary diseases in a single-tertiary center. Methods. All patients with EGI were analyzed retrospectively by retrieving data from a prospectively stored endoscopic database between January 2006 and September 2010. Results. There were 31 cases with EGIs (17 female, 14 male) with a mean age ± SD of 58.03 ± 16.89 years. The majority of cases (17/31; 55%) were ampullary or pancreatic cancers with obstructive jaundice. The major indications for EGI were obstructive jaundice (𝑛=16) and cholangitis (𝑛=9). The EGIs were technically successful in 24 of the 31 cases (77%). The success rate for the first 3 years was 8 of 13 procedures (61.5%) as compared to that of the last 2 years (16/18 procedures (89%); 𝑃=0.072). Twenty-three of the 24 cases (96%) with technical success for stent placement also had clinical success in terms of symptom improvement. The complications were major in 4 (13%) and minor in 7 (23%) patients. Conclusion. The EUS-guided drainage for biliary obstruction, acute cholecystitis, bile leak, and biloma was an attractive alternative and should be handled in expert centers.